การบริหารกิจกรรมนักเรียนด้านการจัดการวงโยธวาทิต : กรณีศึกษาโรงเรียนวัดสุทธิวราราม และโรงเรียนมงฟอร์ตวิทยาลัย - สิทธิ สิทธิการุณย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This research was designed to do the comparative study of the management of student activity in school military bands of Watsuthiwararam School and Monfort College. Problems related to the management of student activity in terms of military band of both schools were also found out. The research indicated that the management of both school military bands are quite similar. It is composed of two sections : the management at the school level, dealing with-policy and general administration, which the principle responsibilities are assigned to the assistant principal, serving as co-ordinator comunicating with the teacher in charge of school military band, and the other section rested with military band student committee of each school. The school military band student committee comprising band leader and assistand band leader taken in charge of overseeing overall activties of the band and condcut other activities as teacher s instruction. The military band student committee can be devided into two groups : group leader and music instrument leaders. Grounp leaders looks over the progress the band activities, while instument leader is responsible for the practice of various kind of music instruments. Both school provided sufficient budgetary fund, proper space and facilities needed, and especially in having trainer to fulfil students with special musical skills. Major problem occurring in both schools in the insufficient skill of teacher in project planing. The other big problem as cited at the Watsuthiwararam school is that having unsuitable place for marching and display practice, while Monfort College complaint is that they have no appropriate place for the concert performance.